Decreased respiratory performance of children and adolescents with myelomeningocele who use a wheelchair – preliminary data - Martins,E.J. (2019)
Myelomeningocele (MMC) is a neural tube defect that often causes spinal cord injury at the thoracolumbar region, as well as sensory and motor paralysis in the lower limbs. This leads to continuous use of a wheelchair and, consequently, a sedentary lifestyle, predisposition to muscle weakness, cardiovascular and respiratory disorders, obesity, and structural alterations in the spine. We assessed the respiratory function and shoulder strength of MMC participants who were wheelchair-users and had no respiratory complaints and compared them to healthy children and adolescents. MMC (n=10) and healthy (n=25) participants of both genders with a mean age of 12.45 years (SD=2.1) were assessed for weight, height, respiratory performance, and isometric peak for shoulder flexors, extensors, abductors, and adductors, using an isokinetic dynamometer. Medullary lesion, functional levels, and abnormal curvatures of the spine were assessed for MMC participants. The level of spinal cord injury for the majority of the MMC participants was high lumbar and they had scoliosis. MMC showed lower values for forced vital capacity, forced expiratory volume at the first second, forced expiratory flow (25–75%), maximal voluntary ventilation, and isometric peak for shoulder flexors and adductors compared to healthy participants. This indicated a decreased vital capacity, respiratory muscle endurance, and shoulder muscle strength.